Phosphorylation of unique domains of Src family kinases - Amata, Irene; Maffei, Mariano; Pons, Miquel (Frontiers in Genetics, 2014)
Members of the Src family of kinases (SFKs) are non-receptor tyrosine kinases involved in numerous signal transduction pathways. The catalytic, SH3 and SH2 domains are attached to the membrane-anchoring SH4 domain through the intrinsically disordered 'Unique' domain, which exhibits strong sequence divergence among SFK members. In the last decade, structural and biochemical studies have begun to uncover the crucial role of the Unique domain in the regulation of SFK activity. This mini-review discusses what is known about the phosphorylation events taking place on the SFK Unique domains, and their biological relevance. The modulation by phosphorylation of biologically relevant inter- and intra- molecular interactions of Src, as well as the existence of complex phosphorylation/dephosphorylation patterns observed for the Unique domain of Src, reinforces the important functional role of the Unique domain in the regulation mechanisms of the Src kinases and, in a wider context, of intrinsically disordered regions in cellular processes.